Menciptakan Lingkungan Inovatif Melalui Kepemimpinan Kepala Sekolah - Ahmad Mustaghfirin; M Khoirul Fikri; Nur Diansyah; Fajar Sidik; Ma’ruf Hidayatullah; Tamrin Fatoni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The principal's goal in creating an innovative environment is to improve the quality of learning, develop student creativity, encourage collaboration between student teachers and parents, facilitate teacher professional development and utilize technology as a support in the learning process. This is considered important. School principals have a significant influence on improving educational standards. They are tasked with managing schools, planning educational events, training teachers, and utilizing and maintaining infrastructure and facilities. The results of this research are that school principals need to take various steps to create an innovative learning environment. These steps include formulating a vision and mission that supports innovation, providing resources, and encouraging collaboration. Through effective leadership, school principals can create an environment that supports creativity, active participation, and a meaningful learning process. The role of the principal in the learning environment is very important to create an atmosphere that is conducive to students' academic and social development. School principals have a crucial role in determining the quality and success of learning in schools. By being a visionary instructional leader, school principals can ensure that every student has the opportunity to reach their maximum potential in learning. In addition, school principals play a role in supporting teacher professional development, creating a conducive learning environment, utilizing data for improvement, and establishing good relationships with the community.